Wan Abdurachman's Role in Formulating the Basic Principles of the Indonesian State in the Constituent Assembly 1956-1959 AD - Hidayati, Nurul; Hamid, Abd Rahman; Setiawan, Agus Mahfudin; Hasanah, Uswatun (Universitas Islam Negeri Sumatera Utara, 2025)
This article discusses the role of Wan Abdurachman in formulating the foundation of the Indonesian state in the Constitutional Assembly from 1956 to 1959. The research employs the historical method, which includes four stages: heuristics, source criticism, interpretation, and historiography. The historical sources were obtained from the National Archives, the National Library, and the official website of the MPR RI. The findings of this study reveal that Wan Abdurachman was the most prominent Islamic figure in Lampung, who, since his youth, was active in nationalist movement organizations based on Islam (the Indonesian Sarekat Islam Party), which made it easy for him to connect with HOS Tjokroaminoto, who developed the ideology of Islamic socialism. This ideology was advocated as the foundation of the Indonesian state in the Constitutional Assembly. This is the important contribution of this study: that Tjokroaminoto formulated Islamic socialism during the national movement period, and Wan Abdurachman fought for it to become the foundation of the Indonesian state in the Constitutional Assembly.